BOUNDARY RE-ASSESSMENT of the METER READING UNIT (MRU) for TENAGA NASIONAL BERHAD, TNB CHERAS - Zulkflee A.; Abdul Khanan M.F.; Umar H.A.; Abdul Rahman M.Z.; Nik Mohd Kamil F. (International Society for Photogrammetry and Remote Sensing, 2023)
Geographic information systems; Information systems; Information use; Travel time; Clustering analysis; Electrical distribution; GIS application; Modelling tools; Remote meter reading; Spatial analysis; Spatial data analysis; Technical loss; Spatial variables measurement